A cross sector evaluation comparing nutrient removal strategies in urban water systems - Hodgson, Brock, author; Sharvelle, Sybil, advisor; Arabi, Mazdak, committee member; Carlson, Ken, committee member; Hoag, Dana, committee member (Colorado State University. Libraries, 2019)
Water supply management and reduction of nutrient pollution from urban water systems are two of the most important issues facing utility managers today. To better protect water supplies, many states have or are establishing total nitrogen (TN) and/or total phosphorous (TP) loading restrictions from urban water systems. Traditionally, these targets are met by wastewater treatment facility (WWTF) improvements, but stringent regulations can make this challenging and costly. As regulations increase it may be necessary or more cost effective to consider additional options for nutrient removal from urban water systems including water management practices or stormwater control measures (SCMs). There are a wide range treatment approaches that can be considered at a WWTF for improving nutrient removal but evaluating these scenarios can be challenging and is traditionally accomplished via mechanistic models specific to individual WWTFs requiring process expertise and a rigorous sampling and analysis program. Water management practices are traditionally considered for water supply improvement, however there is little research to characterize the impact on water quality. There is a need for additional research and tools that facilitate estimating effectiveness of various nutrient removal technologies and consider cross sector strategies and tradeoffs between adoption of practices. To understand the impacts of water management practices, the impact of indoor conservation, source separation, and graywater and effluent reuse on WWTF influent and effluent and downstream water quality was characterized identifying which practices can potentially help meet nutrient reduction targets. For WWTF technologies, previously calibrated and validated mechanistic models were used to develop a simplified empirical model to more easily estimate and compare the effectiveness of various WWTF technologies as a function of influent wastewater quality. The findings from the water management practice evaluation and WWTF treatment comparison provided the framework for conducting an urban water systems evaluation by using the developed empirical models combined with the benefit of stormwater control measures (SCMs) characterized via the Simple Method to evaluate a multitude of strategies for meeting nutrient removal targets in the urban water system. Lastly, this research considered the impacts on biosolids management with the increase of liquid stream removal at the WWTF. The research identified source separation and effluent reuse as frequent part of effective nutrient removal strategies and part of an optimal nutrient removal strategy, and even necessary under stringent nutrient requirements. In terms of wastewater treatment, the benefit of adopting more advanced wastewater treatment processes will be most beneficial in carbon limited WWTFs, and negligible when there is adequate carbon for biological nitrogen and phosphorous removal. This includes sophisticated processes like nitrite shunt and 5-Stage Bardenpho and sidestream processes like struvite precipitation and ammonia stripping. While improvements to WWTF are likely with adoption of stringent nutrient regulations a multi objective optimization identified water management practices and SCMs to be part of all non-dominated nutrient removal strategies. As nutrient requirements become more stringent, the options for WWTFs in terms of processes are limited and frequently a combination of water management practices and SCMs is necessary. This was demonstrated via a systems analysis of cost-effective nutrient removal solutions in urban water systems that can be easily applied to other urban systems because of the empirical models developed with this research. These tools are necessary to help utility managers identify optimal nutrient removal strategies. As utilities invest in improvements to WWTF operations, there may also be notable impacts on biosolids management, primarily in terms of phosphorous, which may limit land application rates resulting in additional cost or disposal of biosolids that historically have been beneficially used in agriculture. These impacts must also be considered by utility managers when considering optimal nutrient removal strategies from urban water systems.
Keywords: stormwater control; water management; wastewater treatment; nutrient pollution